High NAFLD fibrosis score in non-alcoholic fatty liver disease as a predictor of carotid plaque development: a retrospective cohort study based on regular health check-up data in China. (1st January 2021) - Yu, Xinyan; Chen, Chen; Guo, Yi; Tong, Yuling; Zhao, Yi; Wu, Lingyan; Sun, Xue; Wu, Xifeng; Song, Zhenya
Abstract: Purposes: There is increasing concern regarding cardiovascular risk in non-alcoholic fatty liver disease (NAFLD) patients with liver fibrosis. This study aims: (1) to assess the association between NAFLD and liver fibrosis status and the development of carotid plaque (CP), and (2) to identify CP risk factors among general population with different baseline NAFLD and liver fibrosis status. Methods: This retrospective cohort study included 14, 288 adult participants who went for regular health check-ups between 2014 and 2019, in one hospital in Zhejiang, China. NAFLD was diagnosed by abdominal ultrasound and the NAFLD fibrosis score (NFS) was calculated to reflect the extent of liver fibrosis. Cox proportional hazards analyses were applied to assess the risk of CP development across groups with different baseline NAFLD and NFS status. Results: NAFLD participants with high NFS had higher risk of CP compared to non-NAFLD participants (adjusted hazard ratio 1.68, 95% confidence interval [CI] 1.43–1.96, p < .001). Progression from NAFLD free and NAFLD with low NFS to NAFLD with high NFS are associated with 1.56-fold (95% CI 1.21–2.01, p = .001) and 1.43-fold (95% CI 1.11-1.84, p = .006) increased risk of CP, respectively. Risk factors associated with CP vary based on baseline NAFLD and NFS status. Among NAFLD participants with high NFS, hypertension is the only significant risk factor after adjustment for other potential influencing factors. Conclusions: NAFLD and liver fibrosis status can be an independent predictor for CP development regardless of metabolic abnormalities. Hypertension is a major risk factor for CP development among NAFLD patients with high NFS. KEY MESSAGES: Non-alcoholic fatty liver disease (NAFLD) and liver fibrosis status can be an independent predictor for development of carotid plaque. Progression from NAFLD free and NAFLD with low NAFLD fibrosis score (NFS) to NAFLD with high NFS are associated with increased risk of carotid plaque. Risk factors associated with carotid plaque vary based on baseline NAFLD and NFS status, and hypertension plays the most important role among patients with NAFLD and high NFS.